Hubungan Implementasi Patient-Centered Care (PCC) dengan Kepuasaan Pasien Rawat Inap di RSU Martha Friska Brayan Medan - Zubaidah, Siti; Zulfendri, Zulfendri; Theo, Deli (Universitas Malahayati, 2024)
ABSTRACT The preliminary survey revealed that 60% of patients still feel that they are not fully involved in the care process, possibly due to factors such as lack of information provided to the patients, limited time available for healthcare providers, and insufficient therapeutic communication. Moreover, 70% of patients feel that their care is not smoothly coordinated, possibly due to lack of coordination among healthcare providers, inadequate documentation (medical records), and insufficient patient information. The research utilized a quantitative research design, based on the positivist philosophy, to examine a specific population at Martha Friska Hospital in Medan. The population size was unknown, and the sample size was determined using the Lemeshow formula, resulting in 96 individuals. Data collection involved distributing questionnaires to inpatients to assess the impact of patient-centered care on satisfaction levels. Bivariate analysis, specifically the Chi Square test. The study conducted at RSU Martha Friska Brayan Medan in 2024 assessed the implementation of patient-centered care and its impact on inpatient satisfaction. The analysis revealed significant relationships between various aspects of patient-centered care and patient satisfaction. These findings highlight the importance of specific elements of patient-centered care in enhancing overall patient satisfaction. The research findings show that the aspects of patient-centered care (PCC) related to inpatient satisfaction at RSU Martha Friska Brayan Medan are respecting patient choices and judgment, emotional support, physical comfort, and information and education. However, factors such as continuity and transition, service coordination, and involvement of family and friends are not associated with patient satisfaction. Recommendations for RSU Martha Friska Brayan Medan to improve inpatient services include respecting patients' choices, providing physical comfort, emotional support, and health education to patients. Keywords: Implementation, PCC, Patient Satisfaction, Hospital ABSTRAK Survei pendahuluan mengungkapkan bahwa 60% pasien masih merasa bahwa mereka tidak sepenuhnya terlibat dalam proses perawatan, mungkin karena faktor-faktor seperti kurangnya informasi yang diberikan kepada pasien, terbatasnya waktu yang tersedia untuk penyedia layanan kesehatan, dan komunikasi terapeutik yang tidak memadai. Selain itu, 70% pasien merasa bahwa perawatan mereka tidak terkoordinasi dengan lancar, mungkin karena kurangnya koordinasi di antara penyedia layanan kesehatan, dokumentasi (rekam medis) yang tidak memadai, dan informasi pasien yang tidak memadai. Penelitian ini menggunakan desain penelitian kuantitatif, berdasarkan filosofi positivis, untuk memeriksa populasi tertentu di Rumah Sakit Martha Friska di Medan. Ukuran populasi tidak diketahui, dan ukuran sampel ditentukan menggunakan rumus Lemeshow, menghasilkan 96 individu. Pengumpulan data melibatkan penyebaran kuesioner kepada pasien rawat inap untuk menilai dampak perawatan yang berpusat pada pasien pada tingkat kepuasan. Analisis bivariat, khususnya uji Chi Square. Studi yang dilakukan di RSU Martha Friska Brayan Medan pada tahun 2024 menilai implementasi perawatan yang berpusat pada pasien dan dampaknya terhadap kepuasan rawat inap. Hasil penelitian menunjukkan bahwa aspek patient-centered care (PCC) terkait kepuasan rawat inap di RSU Martha Friska Brayan Medan adalah menghargai pilihan dan penilaian pasien, dukungan emosional, kenyamanan fisik, serta informasi dan edukasi. Namun, faktor-faktor seperti kontinuitas dan transisi, koordinasi layanan, dan keterlibatan keluarga dan teman-teman tidak terkait dengan kepuasan pasien. Rekomendasi RSU Martha Friska Brayan Medan untuk meningkatkan pelayanan rawat inap antara lain menghormati pilihan pasien, memberikan kenyamanan fisik, dukungan emosional, dan edukasi kesehatan kepada pasien. Kata Kunci: Implementasi, PCC, Kepuasaan Pasien, Rumah Sakit.